Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Berpikir Kritis Siswa: The Effect of Discovery Learning Model on Students' Critical Thinking Ability - Nurul Amalia Tamsir; Sarintan N. Kaharu; Nurul Kami Sani; Azizah Azizah; Nuraini Nuraini; Sri Wahyuni (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to determine the effect of the Discovery Learning model on the critical thinking skills of fifth-grade students at SD Inpres 2 Besusu. The research employed a quantitative method with a one-group pretest-posttest design. The population of this study consisted of all fifth-grade students at SD Inpres 2 Besusu, totaling 19 students. The sampling technique used was saturated sampling, in which the entire population was used as the sample due to its relatively small size (fewer than 30 individuals). Therefore, the sample in this study was all 19 fifth-grade students at SD Inpres 2 Besusu. Data collection techniques included a critical thinking skills test, observation sheets, and interviews. The data analysis used in this study comprised descriptive and inferential statistical analysis, assisted by the IBM SPSS Statistics version 30 application. Based on the results and analysis of the research data, it can be concluded that there is an influence of the Discovery Learning model on the students' critical thinking skills in class V at SD Inpres 2 Besusu. This can be seen from the posttest results in the IPAS subject, where the average score was 88.37. The Paired Sample T-Test analysis showed a significance value of 0.000, which is less than 0.05, indicating that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This demonstrates that the Discovery Learning model has a positive effect on the critical thinking skills of fifth-grade students at SD Inpres 2 Besusu. This research implies that the implementation of the Discovery Learning model can enhance students' critical thinking skills. Therefore, this model can be more widely integrated into the learning process at SD Inpres 2 Besusu to help students develop analytical and more creative problem-solving skills. Additionally, the findings of this study provide a basis for teachers to use more interactive and discovery-based teaching models to improve the quality of education and students' critical thinking abilities in the future.